2015
DOI: 10.1097/mao.0000000000000701
|View full text |Cite
|
Sign up to set email alerts
|

Does Electrocautery Damage Cochlear Implants?

Abstract: The cochlear implant devices had no evidence of electrical damage by monopolar cautery, even up to levels of 100 W in the temporalis muscle. The maximum voltage change was 22 V, likely resulting from protecting diodes within the implant. Additional study is necessary, but more flexible recommendations regarding electrosurgery in cochlear implant recipients should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 7 publications
(4 reference statements)
0
21
0
Order By: Relevance
“…13 Our patient additionally presented with cochlear implants requiring that we utilize bipolar cautery due to the presumed risk that monopolar cauterization may damage the device and that the heat generated by it may injure auditory neurons. 24 Being limited to bipolar cautery was challenging particularly given our patient's venous collateralization resulting in increased bleeding. Despite manufacturer recommendations, reports in the literature showed that monopolar cautery has not resulted in increased complications when used in the presence of cochlear implants.…”
Section: Discussionmentioning
confidence: 99%
“…13 Our patient additionally presented with cochlear implants requiring that we utilize bipolar cautery due to the presumed risk that monopolar cauterization may damage the device and that the heat generated by it may injure auditory neurons. 24 Being limited to bipolar cautery was challenging particularly given our patient's venous collateralization resulting in increased bleeding. Despite manufacturer recommendations, reports in the literature showed that monopolar cautery has not resulted in increased complications when used in the presence of cochlear implants.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the aforementioned studies, the group did not advocate for cautery use but argued for the consideration of more flexible recommendations from manufacturers. 8 Similarly, Antonelli and Baratelli 10 implanted CIs into fresh cadaveric pigs and performed adenoidectomy with Coblation and monopolar cautery. Monopolar settings were 50 W, and the stimulus was held to the tissue for 15 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…In another cadaveric study by the same group, 10 cautery was applied to the ipsilateral pectoralis major muscle or ipsilateral temporalis muscle at bipolar, monopolar coagulation, and monopolar cut settings of 50 to 100 W. The CI was fully inserted through a cochleostomy anterior to the round window by standard methods. Integrity testing was performed before, during, and after each cautery setting, and the implant was explanted and returned to the manufacturer for in-depth failure analysis to evaluate for any damage to the devices.…”
Section: Discussionmentioning
confidence: 99%